Enhancing Accuracy and Precision in Omni-Angle Edge-Based Modulation Transfer Function Measurements - Kenichiro Masaoka (IEEE Access)
The modulation transfer function (MTF) quantitatively describes the ability of an optical or imaging system to reproduce contrast at various spatial frequencies. The ISO 12233 edge-based method adopted diagonal MTF measurement for sampled imaging systems by analyzing the gradient of a slanted edge captured by the system and estimating MTF as a function of spatial frequency perpendicular to the edge. Pixels in a region of interest (ROI) are projected into a quarter-pixel wide bin array on a horizontal or vertical axis, yielding a $4× $ oversampled edge spread function. However, the accuracy and precision of MTF estimates can degrade considerably at high spatial frequencies for certain edge angles because of the clustering of the projection paths at or around specific locations on the bin array axis. Thus, a novel edge-based method, Omni-sine, was proposed to overcome this limitation by optimizing a noninteger oversampling ratio based on the edge angle. The accuracy and precision of the proposed method were demonstrated through computer simulations using synthesized edge images and through actual measurements with a machine vision camera. Implementing the Omni-sine method does not affect the real-time nature of the edge-based measurement and facilitates MTF anisotropy measurements using multiple nonrectangular ROIs with slanted starburst charts.